Larsemann Hills: Geomorphometric modeling and mapping - Florinsky I.V. (Polar Science, 2023)
Geomorphometric modeling is widely used in geosciences. However, geomorphometric modeling and mapping of Antarctic oases has not been performed so far. This article presents the first results of our work on geomorphometric modeling and mapping of the Larsemann Hills obtained in the frameworks of the 68th Russian Antarctic Expedition in January–April 2023. As input data, we used a fragment of the Reference Elevation Model of Antarctica (REMA). From the extracted and edited digital elevation model, we derived digital models and maps of the following 17 morphometric variables: slope, aspect, horizontal curvature, vertical curvature, mean curvature, Gaussian curvature, minimal curvature, maximal curvature, unsphericity curvature, difference curvature, vertical excess curvature, horizontal excess curvature, ring curvature, accumulation curvature, catchment area, topographic index, and stream power index. We also conducted a field geomorphometric interpretation work to provide correct physical geographic, geological, and geomorphological interpretations of morphometric maps. In the fieldwork, we carried out 54 foot routes with the total length of about 422 km. During the routes, we collected 150 rock samples for further petrological and mineralogical analyses as well as three-dimensional modeling of the samples. Derived morphometric maps can be useful for structural geological and process-oriented hydrological studies. The ultimate goal of the ongoing work is to create a large-scale geomorphometric atlas of Antarctic oases and other ice-free Antarctic territories. journal article